Label-free hyperspectral microscopy with attosecond precision - Herbst, A.; Srivastava, A.; Scheffter, K.; Jun, S.; Petrini, N.; Rubino, A.; Kriegel, I.; Fattahi, H. (2024 IEEE Photonics Conference, IPC 2024 - Proceedings, 2024)
We report on a novel concept for label-free hyperspectral microscopy at near-petahertz frequencies based on direct field-resolved detection of a sample response with attosecond precision. Hyperspectral imaging of an indium tin oxide structure is demonstrated. The technique lays the groundwork for super-resolution label-free hyperspectral imaging.
CRIS-Team Scopus Importer:2025-02-04
Keywords: attosecond precision; electro-optic sampling; field-resolved detection; High-resolution microscopy; Label-free microscopy